Li-Dan-He-Ji Improves Infantile Cholestasis Hepatopathy Through Inhibiting Calcium-Sensing Receptor-Mediated Hepatocyte Apoptosis - Huan Qin (Frontiers in Pharmacology, 2020)
Infantile cholestatic hepatopathy (ICH) is a clinical syndrome characterized by the accumulation of cytotoxic bile acids in infancy, leading to serious liver cirrhosis or liver failure. The aetiology of ICH is complicated and some of them is unknown. Regardless of the aetiology, the finial pathology of ICH is hepatocyte apoptosis caused by severe and persistent cholestasis. It is already known that activation of calcium-sensing receptor (CaSR) could lead to the apoptosis of cardiomyocytes. However, the mechanism by CaSR-mediated cholestasis-related hepatocyte apoptosis is not fully understood. Li-Dan-He-Ji (LDHJ), a Traditional Chinese Medicine prescription, was developed to treat ICH. Another aim of this study was to investigate the possible mechanisms of LDHJ in cholestasis-related hepatocyte apoptosis. Using the primary hepatocytes, we first investigated the molecular mechanism of CaSR-mediated hepatocyte apoptosis in cholestasis. Then we prepared LDHJ granules and used ultra-high-performance liquid chromatography to identify the predominant drugs; confirmed the stability of the main substances; and for cell experiments screened forsythoside-A, emodin and chlorogenic acid as the three active substances of LDHJ granules. In the young rats with ANIT-induced intrahepatic cholestasis and the primary hepatocytes with TCDC-induced cholestasis-related hepatocyte apoptosis, the levels of liver injury and cholestasis-related biomarkers, calcium-sensing receptor (CaSR), hepatocyte apoptosis, Bax/Bcl-2 ratio, Cytochrome-C, caspase-3, phosphorylated-c-Jun NH2-terminal kinase (p-JNK)/JNK, and p-P38/P38 were all increased, while the levels of p-extracellular signal-regulated kinase (p-ERK)/ERK were decreased. However, LDHJ granules and its three active substances effectively reversed these changes. Furthermore, the three active substances reduced the increases in the intracellular calcium concentration ([Ca2+]i) and ROS levels and attenuated the dissipation of the mitochondria membrane potential in the TCDC-induced primary hepatocytes. The opposite results were obtained from the TCDC-induced primary hepatocytes treated with an agonist of CaSR (GdCl3) plus forsythoside-A, emodin or chlorogenic acid. Based on the results from in vivo and in vitro studies, LDHJ functions as an antagonist of CaSR to regulate hepatocyte apoptosis in cholestasis through the mitochondrial pathway and mitogen-activated protein kinase pathway.